2023
DOI: 10.3389/fcimb.2023.1141274
|View full text |Cite
|
Sign up to set email alerts
|

The antiviral activity of a small molecule drug targeting the NSP1-ribosome complex against Omicron, especially in elderly patients

Abstract: IntroductionWith the emergence of SARS-CoV-2 mutant strains, especially the epidemic of Omicron, it continues to evolve to strengthen immune evasion. Omicron BQ. 1 and XBB pose a serious threat to the current COVID-19 vaccine (including bivalent mRNA vaccine for mutant strains) and COVID-19-positive survivors, and all current therapeutic monoclonal antibodies are ineffective against them. Older people, those with multimorbidity, and those with specific underlying health conditions remain at increased risk of C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 31 publications
0
6
0
Order By: Relevance
“…A bioinformatics drug screening based on SARS-CoV-2 Nsp1 structure was performed and around 7,500 compounds from three databases were collected for molecular docking and in silico evaluation ( Shen et al., 2023 ). The data suggested that golvatinib, gliquidone, and dihydroergotamine were superior to other compounds in binding conformation and free energy ( Shen et al., 2023 ). These drugs could interfere with SARS-CoV-2 Nsp1 binding to 40S protein, resulting in inhibition of SARS-CoV-2 infection ( Shen et al., 2023 ).…”
Section: Iav Ns1 and Sars-cov-2 Nsp1 As Targets For Antiviral Researchmentioning
confidence: 99%
See 2 more Smart Citations
“…A bioinformatics drug screening based on SARS-CoV-2 Nsp1 structure was performed and around 7,500 compounds from three databases were collected for molecular docking and in silico evaluation ( Shen et al., 2023 ). The data suggested that golvatinib, gliquidone, and dihydroergotamine were superior to other compounds in binding conformation and free energy ( Shen et al., 2023 ). These drugs could interfere with SARS-CoV-2 Nsp1 binding to 40S protein, resulting in inhibition of SARS-CoV-2 infection ( Shen et al., 2023 ).…”
Section: Iav Ns1 and Sars-cov-2 Nsp1 As Targets For Antiviral Researchmentioning
confidence: 99%
“…The data suggested that golvatinib, gliquidone, and dihydroergotamine were superior to other compounds in binding conformation and free energy ( Shen et al., 2023 ). These drugs could interfere with SARS-CoV-2 Nsp1 binding to 40S protein, resulting in inhibition of SARS-CoV-2 infection ( Shen et al., 2023 ). However, studies to confirm the antiviral properties of these potential antiviral compounds against SARS-CoV-2 were not conducted in this study ( Shen et al., 2023 ).…”
Section: Iav Ns1 and Sars-cov-2 Nsp1 As Targets For Antiviral Researchmentioning
confidence: 99%
See 1 more Smart Citation
“…CEP was an inexpensive and well-established medication in Japan, authorized for more than 70 years. As early as 30 years ago, CEP was applied in the empirical treatment of pneumoconiosis in China, with good results ( Shen et al, 2023 ). Presently, no fewer than four pharmaceutical enterprises in China have been approved to manufacture and distribute CEP for the prevention and treatment of cancer patients with leukopenia endangered by radiotherapy and chemotherapy.…”
Section: A Brief Overview and Current Uses Of Cepmentioning
confidence: 99%
“…It has been reported that amontelukast sodium hydrate may be the potential inhibitor for SARS-CoV-2 Nsp1 [ 100 ]. Additionally, the researchers found that Golvatinib, Gliquidone, and Dihydroergotamine bind to Nsp1 and have a potential inhibitory effect against SARS-CoV-2 [ 101 ].…”
Section: Virus-targeting Antiviralsmentioning
confidence: 99%